The Utilization of E-Commerce for Developing of MSME Product - Windy Dermawan; Henike Primawanti (Universitas Serang Raya, 2021)
Pandemic of the Covid-19 has had an impact on various sectors, one of which is the MSME (Micro, Small, Medium Enterpise) sector. The implementation of the Large-Scale Social Restriction (PSBB) policy has provided challenges for the economic life of citizens, especially entrepreneurs who have to develop their businesses by utilizing e-commerce. However, not all MSMEs are ready to enter the digital market. The purpose of this activity is to provide understanding and readiness to MSME players regarding the importance of entering e-commerce to market their products. This community empowerment uses the methods of extension, consultation, and Problem Based Learning. This activity is able to contribute to participants in increasing their understanding of the importance of developing MSME product marketing through the internet by opening markets through the marketplace. Several participants have also been guided to be able to open accounts in the marketplace in marketing their products.